The National Symposium “The Monument - tradition and future” (Confluenţe Bibliologice, 2013)
The Edition XV of the Symposium " The Monument-Tradition and future", held in Iasi, between 14 and 17 October 2013, marks the continuation of a tradition in which experts from diﬀerent ﬁelds make a remarkable contribution to the value of monuments but also methods of research, restoration and preservation.
Keywords: dissemination of information